An early origin of secondary growth: Franhueberia gerriennei gen. et sp. nov. from the Lower Devonian of Gaspé (Quebec, Canada)1. Issue 4 (1st April 2013) - Hoffman, Laurel A.; Tomescu, Alexandru M. F.
Abstract : Premise of the Study: Secondary xylem (wood) produced by a vascular cambium supports increased plant size and underpins the most successful model of arborescence among tracheophytes. Woody plants established the extensive forest ecosystems that dramatically changed the Earth's biosphere. Secondary growth evolved in several lineages in the Devonian, but only two occurrences have been reported previously from the Early Devonian. The evolutionary history and phylogeny of wood production are poorly understood, and Early Devonian plants are key to illuminating them. Methods: A fossil plant preserved anatomically by cellular permineralization in the Lower Devonian (Emsian, ca. 400–395 million years old) Battery Point Formation of Gaspé Bay (Quebec, Canada) is described using the cellulose acetate peel technique. Key Results: The plant, Franhueberia gerriennei Hoffman et Tomescu gen. et sp. nov., is a basal euphyllophyte with a centrarch protostele and metaxylem tracheids with circular and oval to scalariform bordered multiaperturate pits (P‐type tracheids). The outer layers of xylem, consisting of larger‐diameter P‐type tracheids, exhibit the features diagnostic of secondary xylem: radial files of tracheids, multiplicative divisions, and a combination of axial and radial components. Conclusions: Franhueberia is one of the three oldest euphyllophytes exhibiting secondary growth documented in the Early Devonian. Within the euphyllophyte clade, these plants represent basal lineages that predate the evolution of stem‐leaf‐root organography and indicate that underlying mechanisms for secondary growth became part of the euphyllophyte developmental toolkit very early in the clade's evolution.